Heat storage for the coupling of Waste Heat Recovery and hydrogen production in a Solid-Oxide electrolyser - Fabiani Titouan; Tochon Patrice; Le Pierres Nolwenn; Dumoulin Pierre (MATEC Web of Conferences)
The dihydrogen molecule H2 is set to play a major role in future energy systems, both as a component of fuels or synthesis gases, and as an energy carrier for long-term electricity storage. Water electrolysis technologies based on renewable electricity represent a credible decarbonized alternative to current H2 production by steam reforming, which emits high levels of CO2. Among these, Solid Oxide Electrolysis Cells (SOEC) have significant potential for achieving low-cost, decarbonized production (Reytier et al., 2015). To operate efficiently, a SOEC system needs a thermal management system capable of heating incoming streams up to the SOEC operating temperature (700-850°C). For the superheating stage, between 150°C and the operating temperature, the heat from the SOEC outflows is generally recovered in high-temperature exchangers (Min, Choi and Hong, 2022). Consequently, dry steam generation represents the largest thermal energy consumption of the system and has a significant impact on the overall efficiency of hydrogen production. In this work, a thermal system is designed to generate steam from waste heat in the form of industrial gases. This thermal system is modelled using Dymola software based on the Modelica language. In this way, it is possible to dynamically simulate the thermal system response to variations in the flow rate and temperature of the industrial waste heat. In the proposed thermal architecture, the heat from the waste heat flux is extracted through a tube bundle heat exchanger to heat a primary thermal oil loop. The hot thermal oil is then used in a plate steam generator to, first, heat the secondary flow of liquid water up to the saturation temperature, and second, evaporate water to produce steam. High-temperature heat exchangers are finally used to recover heat from the SOEC system output streams. Thermocline sensible storage is added to the primary oil loop to maintain a constant secondary flow of steam to the SOEC despite the highly variable availability of industrial waste heat. An electric heater is also added to the oil loop, as a back-up. The entire thermal system is controlled by various pumps and valves located in the oil loop and at the level of the industrial exhaust. Ultimately, real temperature and flow data from the exhaust gases of an industrial plant are used to size and test the thermal architecture. The heat exchangers are modeled in 0D using the LMTD method. A 1-tank thermocline thermal storage with a rock bed is chosen in this study. The use of a rock bed reduces the total amount of expensive thermal oil contained in the thermal storage system, and therefore its total installation cost. This also influences the thermal stratification of the fluid. The thermocline storage is modeled in 1D along the vertical axis. Conductoconvective exchange between the oil and the rocks, conduction between the rocks and conduction in the oil in the vertical direction are considered. Finally, the SOEC system is represented by a stationary model based on experimental results. The thermal system is designed and controlled to maintain the hydrogen production in the SOEC constant during the operation of the industrial plant, whatever the temperature and flow rate of the recoverable industrial gases. When too little thermal power is available from the industrial gases, it is possible to switch on the electric heater or extract hot oil from the thermal storage. The sizing of the various components and the control strategy are studied with the aim of optimizing the thermal architecture according to the following criteria: energy efficiency, power consumption and cost of dihydrogen production. By implementing the steam generation system described in this work, the overall power consumption and operating costs of the hydrogen production system can be reduced by around 15%.